Hansenia pinnatiinvolucellata is conspecific with H. weberbaueriana (Apiaceae) based on morphology and molecular data - Jia, Sheng-Bin; Guo, Xian-Lin; Zhou, Song-Dong; He, Xing-Jin (Phytotaxa, 2019)
Hansenia pinnatiinvolucellata and H. weberbaueriana have been recorded to co-occur in Hengduan Mountains and adjacent regions. However, there were no reliable distinguishing characters to identify them. In our research, we explored key morphological characters through field work, specimen examinations and original literature reviews and reconstructed the phylogeny based on nuclear ITS regions, to determine the relationship between H. pinnatiinvolucellata and H. weberbaueriana. Morphological results indicated that the key, unique morphological characters (entire or pinnati bracteoles longer than pedicels and fruit with 3 ribs) of H. pinnatiinvolucellata were occurs simultaneously in some populations of H. weberbaueriana. Phylogenetic analyses also reveal that H. pinnatiinvolucellata and H. weberbaueriana are nested together. So, H. pinnatiinvolucellata should be a synonym of H. weberbaueriana.